Genetic analysis of vitamin D related genes in Canadian multiple sclerosis patients. Canadian Collaborative Study Group. - Steckley, J; Dyment, D; Sadovnick, A; Risch, N; Hayes, C; Ebers, G (2000)
The objective of this study was to investigate genes involved in the metabolism and function of vitamin D as candidate genes for genetic susceptibility to MS. Restriction fragment length polymorphisms and highly polymorphic microsatellite markers within or very close to the 1,25(OH)2D3 receptor (VDR) [12q14], the vitamin D binding protein (DBP) [4q12], and the 25(OH)D2 1alpha-hydroxylase [12q13] loci were analyzed for linkage or association with MS. We found no evidence for linkage or association of these candidate genes with MS in the Canadian population.